Reducing length of hospital stay with colchicine - Özlem Karakaş; Abdulsamet Erden; Serdar Can Güven; Berkan Armağan; Enes Seyda Sahiner; Ali Can Kurtipek; Osman Inan; Emin Gemcioglu; İhsan Ateş; Ahmet Omma; Orhan Küçüksahin (Journal of Infection in Developing Countries)
Introduction: Colchicine is an ancient agent with well-known anti-inflammatory effects and commonly used in treatment of hyperinflammatory conditions. It has been argued that colchicine could be an appropriate treatment option in COVID-19 to control hyperinflammatory response. Here in this study, we aimed to investigate the impact of colchicine on outcomes of COVID-19 in our inpatient cohort.